Paresthesia during orthodontic treatment: case report and review. - Monini, André da Costa; Martins, Renato Parsekian [UNESP]; Martins, Isabela Parsekian; Martins, Lídia Parsekian (My University, 2011)
Paresthesia of the lower lip is uncommon during orthodontic treatment. In the present case, paresthesia occurred during orthodontic leveling of an extruded mandibular left second molar. It was decided to remove this tooth from the appliance and allow it to relapse. A reanatomization was then performed by grinding. The causes and treatment options of this rare disorder are reviewed and discussed. The main cause of paresthesia during orthodontic treatment may be associated with contact between the dental roots and inferior alveolar nerve, which may be well observed on tomography scans. Treatment usually involves tooth movement in the opposite direction of the cause of the disorder.
Keywords: adult; case report; cephalometry; computer assisted tomography; female; human; innervation; instrumentation; lip disease; malocclusion; mandibular nerve; methodology; orthodontics; paresthesia; periodontal disease; premolar tooth; radiography; review; three dimensional imaging; tooth root; Bicuspid; Cephalometry; Female; Humans; Imaging, Three-Dimensional; Lip Diseases; Malocclusion, Angle Class II; Mandibular Nerve; Occlusal Adjustment; Paresthesia; Tomography, X-Ray Computed; Tooth Movement; Tooth Root; Young Adult